The Crisis of Human Rights. On the Importance and Timeliness of their Catholic Critique - Gierycz, Michał (Chrześcijaństwo-Świat-Polityka, 2024)
Human rights, as they developed after the Second World War, were intended to protect the objective goods necessary for the development of the human person. As such, they represented an attempt to restore modern politics’ access to the natural moral law. Although human rights are now treated as a “litmus test” for the legitimacy of democracy, their very nature is undergoing a metamorphosis. Along with demands for the recognition of abortion as a human right and same-sex relationships as marriage, they are even becoming a negation of a universal moral law. This article discusses, with reference to the Catholic critique of human rights, the possible reasons for the metamorphosis of human rights that is taking place before our eyes, as well as possible ways out of the “dead end” of the practical negation of human dignity.